Discourse on Blasphemy In Ibn Abdulwahhāb's Kitabut-Tawhid, Vis-À-Vis Non-Muslims’ Attack on Islam In Yorubaland (LPPM Institut Al-Ma`arif Way Kanan Lampung, 2024)
Blasphemy has become a common practice among non-Muslims in Nigeria, most especially among the people in the northern part of the country. Muslims in the north are commonly reacting to this act. Their actions include the killing of the perpetrators. The thrust of this work is to discuss the relevance of the discourse on the blasphemy of Shaykh Muhammad Ibn AbdilWahhab in his book of Tawhīd. The methods employed are analytical and historical. The analytical method helped in analyzing the issue as rampant in the country, most especially in the north and how is tremendously uncommon in Yorubaland. The historical method also assisted in tracing the histories of blasphemous cases in Nigeria. The major findings in the work include the concept of blasphemy in Islam, Christianity, Judaism and Hinduism, among others. So also, the cases of blasphemy in Nigeria: Yorubaland in focus, however, includes the current issue i.e. the case of Abdul-Azeez Adegbola and TaloLohun (who is God). More so, the work encapsulates the punishment of blasphemy in Islam. However, the statements of scholars of Islam are mentioned. The work was concluded and certain recommendations were mentioned, to curb the menace of blasphemy in Nigeria and also a way of advising the Muslims in doing away with jungle justice but rather referring the cases to the appropriate authorities